Nanostructured Lipid Carriers (NLC) as Vehicles for Topical Administration of Sesamol: In Vitro Percutaneous Absorption Study and Evaluation of Antioxidant Activity - Puglia, Carmelo; Lauro, Maria Rosaria; Offerta, Alessia; Crascì, Lucia; Micicchè, Lucia; Panico, Anna Maria; Bonina, Francesco; Puglisi, Giovanni (Planta Medica, 2017)
Sesamol is a natural phenolic compound extracted from Sesamum indicum seed oil. Sesamol is endowed with several beneficial effects, but its use as a topical agent is strongly compromised by unfavorable chemical-physical properties. Therefore, to improve its characteristics, the aim of the present work was the formulation of nanostructured lipid carriers as drug delivery systems for topical administration of sesamol.Two different nanostructured lipid carrier systems have been produced based on the same solid lipid (Compritol® 888 ATO) but in a mixture with two different kinds of oil phase such as Miglyol® 812 (nanostructured lipid carrier-M) and sesame oil (nanostructured lipid carrier-PLUS). Morphology and dimensional distribution of nanostructured lipid carriers have been characterized by differential scanning calorimetry and photon correlation spectroscopy, respectively. The release pattern of sesamol from nanostructured lipid carriers was evaluated in vitro determining drug percutaneous absorption through excised human skin. Furthermore, an oxygen radical absorbance capacity assay was used to determine their antioxidant activity.From the results obtained, the method used to formulate nanostructured lipid carriers led to a homogeneous dispersion of particles in a nanometric range. Sesamol has been encapsulated efficiently in both nanostructured lipid carriers, with higher encapsulation efficiency values (> 90 %) when sesame oil was used as the oil phase (nanostructured lipid carrier-PLUS).In vitro evidences show that nanostructured lipid carrier dispersions were able to control the rate of sesamol diffusion through the skin, with respect to the reference formulations.Furthermore, the oxygen radical absorbance capacity assay pointed out an interesting and prolonged antioxidant activity of sesamol, especially when vehiculated by nanostructured lipid carrier-PLUS.
Keywords: Sesamum indicum; Pedaliaceae; NLC; in vitro percutaneous absorption; Franz cells; DSC; ORAC assay